Manthan Digital Inclusion Award: Status Quo India - Anil Hirwade, Mangala (Journal of Information and Knowledge, 2010)
Technology by itself does not inspire but content does. To promote creation of e-Content, to facilitate e-inclusion and to bridge digital divide, awards have been initiated at international and national levels. World Summit Awards have been initiated at the international level and Manthan e-Content award within India. Manthan award is given for various categories like e-Learning, e-Culture, e-Science, e-Government, e-Health, e-Business, e-Entertainment, e-Inclusion, e-Education, e-News, e-Localization, e-Environment, e-Youth, M-Content, etc. This paper analyses the statewise and categorywise distribution of these awards during 2003-2009. It also lists the winners under each category. During 2003-08, 12 projects were declared as winners under e-inclusion category. This paper also takes a brief overview of these 12 initiatives.